THE EFFECT OF AUDITOR COMPETENCY, EXPERIENCE, AND ETHICS ON AUDIT QUALITY (EMPIRICAL STUDY OF KAP IN JAKARTA AREA) - Nugroho, Vidyarto (LPPM Universitas Bina Bangsa, 2025)
The public accounting profession is responsible for raising the trustworthiness of financial statements so that consumers have trustworthy financial data on which to base their decisions. This study aims to analyze the influence of competence, experience, and ethics of the auditor profession on the audit quality of Public Accountants at Public Accounting Firms in Jakarta. Data analysis techniques using SEMPLS The study results show that auditor competence affects audit quality because auditors actively participate in training to obtain knowledge updates needed in business. Auditor experience also influences audit quality. Auditors are involved in analyzing and preparing audit reports during work. Auditor ethics affects audit quality because auditors maintain independent thought and action when conducting audits